Posterior axilla sling traction: a new technique for severe shoulder dystocia. Issue 3 (20th March 2019) - Hoek, Jeffrey; Verkouteren, Babette; van Hamont, Dennis
Abstract : We describe a case of severe shoulder dystocia where, after failing of the known techniques, the posterior axilla sling traction technique was applied successfully. This technique was first described in 2009 by Hofmeyr and Cluver and must be considered at severe cases of shoulder dystocia where all other non-invasive techniques have failed.